PROFIL KEMAMPUAN BERPIKIR REFLEKTIF SISWA SMP DALAM MEMECAHKAN MASALAH MATEMATIKA STANDAR PISA DITINJAU DARI PERBEDAAN GENDER - Fahruh Juhaevah (MATEMATIKA DAN PEMBELAJARAN, 2017)
This research aimed to describes profile of students’ reflective thinking ability in junior high school within solved mathematical in standardized PISA form problem based on gender different. Reflective thinking has theree components, such as reacting, comparing, and contemplating for each Polya’s problem solving steps. Subject consists of two students, one male and one female in SMPN 1 Bulukumba, Sulawesi Selatan. Subjects are choosen based on mathematical ability test. Data of research is obtained by the result of problem solving test and interviewed that do twice. The second test is data triangulation that make sure validation of research data. The result of test and interview is used to describe profile of students’ reflective thinking within solved problem. The result of research shows generally male student does reacting, comparing, and contemplating at the understanding and looking back step, but male student does not compare at the planning and carrying out step. Female student does all components of reflective thinking at the understanding and looking back step, but female student does not compare at the planning and carrying out step. Male student does compare at the planning but male student does not compare at the carrying out step in quantity problem. Male student does not compare at planning step but male student do compare at the carrying out step in change and relationship problem. Female student do all components of reflective thinking in PISA problem that related to change and relationship problem.